DROTAVERIN VERSUS EPIDOSIN IN CERVICAL DILATION DURING LABOR - SAILAJA KAZA; LAKSHMI RENUKAA; KAMBHAM BHASKAR SUNEETHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to compare the efficacy and safety of drotaverine hydrochloride and epidosin on cervical dilatation. Methods: A total of 80 patients (aged 20–30 years) including both primigravidae and multigravida labor were divided randomly into two groups with 40 patients in each. The drotaverin (D) and epidosin (V) groups were given intravenously, 40 mg drotaverine hydrochloride to the former with every 2 h for a maximum of 3 doses and 8 mg epidosin to the latter with maximum of 6 doses half an hour apart. Results: The mean duration of active phase of labor (hour) was significantly lower in the drotaverin group compared to epidosin group. Furthermore, the cervical dilatation rate was significantly faster in the drotaverin group. There was a significantly higher probability of faster delivery among women who were given drotaverin. The oxytocin augmentation rate, incidence of prolonged labor, labor pain scores, mode of delivery, and maternal and neonatal outcomes were not significantly different among the groups. Conclusion: This study concluded that drotaverin is a new aid in the management of a convenient, shorter, physiological, and uncomplicated delivery.